Sclerotherapy for dilated veins of atypical localization - V. Yu. Bogachev; Ya. O. Grusha; V. N. Lobanov (Амбулаторная хирургия)
The article describes the method of aesthetic correction of dilated non-varicose superficial veins localized on the face, décolleté and upper extremities. It is concluded that the various sclerotherapy options are highly efficient and safe in these clinical situations.